High-strength PP material and application thereof in decorative film

By adding chlorine-containing compounds, gamma-alumina and pyrodiborate to the PP material, combined with plasma treatment and surfactant treatment, the mechanical strength and antibacterial properties of PP materials are improved, and the decoration is solved The poor mechanical properties of the membrane and insufficient antibacterial properties have achieved improvements in puncture resistance and antibacterial effects.

CN119144034AInactive Publication Date: 2024-12-17ZHEJIANG JINSHENG DEOCRATION MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411659509.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The decorative films of existing PP material have poor mechanical properties and insufficient antibacterial properties, which lead to the decorative films being easily damaged and corroded during use.

Method used

By preparing high-strength PP materials, including base layer, pigment layer and anti-wear layer, plasma treatment and surfactivity are carried out using components such as chlorine-containing compounds, gamma-alumina, phenolic acid esters and cubic boron nitride, etc. , and improve the mechanical strength and antibacterial properties of the material.

Benefits of technology

The decorative film with high puncture strength, low wear rate and good antibacterial properties of high-strength PP materials is achieved, extending service life and reducing corrosion risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144034A_ABST
    Figure CN119144034A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of decorative films, in particular to a high-strength PP material and application thereof in decorative films. The prepared high-strength PP material is applied to a decorative film, and the technical problems that the decorative film is low in mechanical strength and poor in anti-corrosion and antibacterial performance are solved. The high-strength PP material is finally prepared by preparing the base layer and preparing the pigment layer and the wear-resistant layer on the surface of the base layer, and the high-strength PP material is applied to the surface of wooden furniture to obtain the decorative film. The raw material dosage of the base layer is changed; adjusting the dosage of raw materials for preparing the bis (pinacol) diboronic acid modified ethyl acrylic acid; the dosage of the cubic boron nitride, the wear-resistant layer and the oxabicyclo heptane is changed; cubic boron nitride is used for loading antibacterial liquid; performing plasma treatment on the PP material; the prepared high-strength PP material is good in mechanical property, and the decorative film is high in strength and good in antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of decorative films, in particular to a high-strength PP material and an application thereof in decorative films. Background Art

[0002] With the improvement of people's safety awareness and living standards, people have a higher demand for decorative films applied to the surface of paint-free furniture. The raw materials for decorative films on the surface of wooden products usually include decorative veneer, melamine paper, impregnated film paper, polyvinyl chloride (PVC), polypropylene (PP) film and polyester film (PET), among which PP film is the most widely used. PP film is a decorative film applied to the surface of paint-free furniture made of polypropylene. Its visual effect is close to natural wood grain and it is environmentally friendly. It is widely used.

[0003] Decorative film has a protective effect on furniture. Low hardness and poor scratch resistance will affect the aesthetics and performance of furniture. Patent CN115926233A discloses a scratch-resistant PP decorative film and its preparation method. Under the action of initiator and curing agent, nano-silicon dioxide, 4,4'-dihydroxybenzophenone, calcium carbonate, reinforcing agent, γ-mercaptopropyltrimethoxysilane, titanate and silane coupling agent react to obtain a scratch-resistant coating, which is applied to the surface of the PP base layer to obtain a scratch-resistant coating. The prepared PP decorative film has high hardness and good wear resistance.

[0004] When the decorative film is applied to the surface of wooden products, the irregular surface will cause the PP film to have a poor coating effect, resulting in surface cracks and local fractures, which will affect the aesthetics of the decorative film. Patent CN109988334B discloses a method of using plasma to modify the surface of PP decorative film. By subjecting the surface of the PP decorative film to plasma modification, physical etching and chemical modification occur, the surface tension and chemical activity are improved, the adhesion of the paint film on the surface of the PP decorative film is improved, and the decorative effect is improved. In addition, the thermoplastic acrylic resin modifier and the surfactant-modified nano-additive added to the primer can improve the physical penetration and cross-linking reaction of the coating on the surface of the PP decorative film, thereby improving the coloring and adhesion. However, the plasma treatment only modifies the polymer surface, and it is difficult for the coating to penetrate into the interior of the polypropylene material.

[0005] In addition, wooden furniture is susceptible to corrosion by various bacteria and fungi during use, and the poor antibacterial property of the decorative film will reduce the durability of the material. Patent CN115891361A discloses an antibacterial PP decorative film and its preparation method. The decorative film is composed of a PP base layer, a printed pattern layer and an antibacterial layer from top to bottom. Nano-conductive silver glue is creatively added to the antibacterial layer as an antibacterial material. The adhesion promoter, flame retardant and other additives solve the problems of poor antibacterial effect and short antibacterial life. In addition, patent CN115838512A discloses a composite reinforced PP decorative film and its preparation method, in which the added phenolic antioxidant, amine antioxidant and phosphorus-based auxiliary antioxidant, thioether auxiliary antioxidant, and thioester antioxidant synergistically prevent the decorative film from yellowing and powdering; polyolefin elastomer and EPDM rubber toughening agent are added to reduce the brittleness of the decorative film; lubricants such as stearic acid and butyl stearate are added to improve processing fluidity; and the reaction temperature is controlled to ensure the stability of the material.

[0006] In the prior art, there are still problems that the PP material decorative film has poor mechanical properties and poor antibacterial properties.

[0007] Therefore, a high-strength PP material and its application in decorative film are proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a high-strength PP material and its application in a decorative film. The high-strength PP material prepared by preparing a base layer, a pigment layer and a wear-resistant layer is applied to the decorative film and has good mechanical strength and antibacterial properties. By controlling the type and amount of chlorine-containing compounds, the amount of γ-alumina and the reaction temperature are changed; the material prepared by ethyl acrylic acid and biboric acid pinacol ester is applied to the pigment layer and the wear-resistant layer; cubic boron nitride is modified, and the amount of components and silane in the antibacterial liquid are adjusted. The high-strength PP material has high puncture resistance and low wear rate. By treating the polypropylene masterbatch with surfactant and then plasma treatment, the decorative film has high puncture resistance and good antibacterial properties. By adjusting the dosage ratio of the antibacterial components, the obtained decorative film has good antibacterial properties.

[0009] To achieve the above object, the present invention provides the following technical solutions: In one aspect, the present invention provides a high-strength PP material, comprising the following components: a base layer, a pigment layer and an anti-wear layer; The raw materials for preparing the base layer include 95 parts of PP material, 3.8-6.7 parts of chlorine-containing compound and 2.5-4.0 parts of γ-alumina in parts by mass; The raw materials for preparing the pigment layer include 65 parts of bis(pinacol)diboron acid ester-modified ethyl acrylic acid, epoxy acrylate, 28.0-30.4 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane and 12.0 parts of tripropylene glycol diacrylate; The raw materials for preparing the anti-wear layer include 4,5-dichloro-2-n-octyl-3-isothiazolinone, 2,6-di-tert-butyl-p-methylphenol and sodium hypophosphite, 43-53 parts of cubic boron nitride, and 15-40 parts of the raw materials for the anti-wear layer; The raw materials for preparing the PP material include 3.0-5.0 parts of surfactin; The PP material is prepared at 170-190° C. The PP material is subjected to plasma treatment to obtain the base layer. The plasma treatment speed is 0-5 m·min -1 , discharge power is 1.5-4kw; The base layer is dried at 25-70°C; The raw materials for preparing the ethyl acrylic acid modified with pinacol diborate include 22.0-25.2 parts of ethyl acrylic acid, 20.3-24.0 parts of pinacol diborate and 0.2-1.0 parts of palladium chloride; The components of the anti-wear layer raw material include 20-28 parts of oxabicycloheptane; In terms of parts ratio, the usage ratio of 4,5-dichloro-2-n-octyl-3-isothiazolinone, 2,6-di-tert-butyl-p-methylphenol and sodium hypophosphite is 5.6-8.6:8-13:5-7.4; The chlorine-containing compound is one of 4,5-dichloro-2-n-octyl-3-isothiazolinone and difenoconazole.

[0010] Preferably, the processing speed of the plasma treatment is 1-5 m·min -1 .

[0011] Preferably, the base layer is dried at 55-70°C.

[0012] Preferably, the preparation method of the PP material is as follows: dissolving the surfactin in a mixed solvent to obtain a surfactin solution; mixing a polypropylene masterbatch with the surfactin solution to obtain a polypropylene dispersion; heating the polypropylene dispersion, and melting and stirring it under sealed conditions for 12 hours to obtain a modified polypropylene melt; transferring the modified polypropylene melt to an extruder, extruding it, and drying it to obtain the PP material.

[0013] Preferably, the ratio of the surfactin to the mixed solvent is 1:200; the ratio of ethanol to N,N-dimethylformamide in the mixed solvent is 3:2.

[0014] Preferably, the method for preparing the base layer is as follows: subjecting the PP material to the plasma treatment to prepare a surface-treated PP material; dissolving the chlorine-containing compound in ethanol to obtain a surface treatment solution; adding the γ-alumina and concentrated sulfuric acid to the surface treatment solution, and ultrasonicating for 15 minutes to obtain a mixed solution; the ratio of the chlorine-containing compound to the ethanol is 1:75; uniformly coating the mixed solution on one side of the surface-treated PP material, and drying to obtain the base layer.

[0015] Preferably, the preparation method of the bis(pinacol)diboron acid ester modified ethyl acrylic acid is as follows: dissolving the ethyl acrylic acid in N,N-dimethylformamide and dimethyl sulfoxide to obtain an ethyl acrylic acid solution; the amount ratio of the ethyl acrylic acid to the N,N-dimethylformamide and the dimethyl sulfoxide is 1:100:200; placing the ethyl acrylic acid solution, the bis(pinacol)diboron acid ester, potassium acetate and the palladium chloride in an oil bath at 85°C, reacting for 6 hours and then cooling to room temperature to obtain the bis(pinacol)diboron acid ester modified ethyl acrylic acid solution; adding water to the bis(pinacol)diboron acid ester modified ethyl acrylic acid solution, filtering, extracting with ethyl acetate, washing with water, drying with anhydrous sodium sulfate, and removing the solvent to obtain the bis(pinacol)diboron acid ester modified ethyl acrylic acid.

[0016] Preferably, the preparation method of the pigment layer is as follows: the epoxy acrylate is placed in a three-necked flask, the temperature is set to 70°C, concentrated sulfuric acid, ferric chloride and benzophenone are added thereto under stirring, and the modified epoxy acrylate is refluxed for 5 hours to obtain the modified epoxy acrylate; the bis(pyridinium)boron acid ester-modified ethyl acrylic acid and azobisisobutyronitrile are added to the modified epoxy acrylate, and the pigment layer precursor is refluxed; the 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane is added to the pigment layer precursor, the concentrated sulfuric acid is added, the temperature is increased to 80°C, the reaction is continued for 6 hours, and after filtering and drying to remove the solvent, the tripropylene glycol diacrylate, triethylenetetramine, methacrylic acid glycidyl ether, sesame, triarylsulfonium salt, water-based pigment and alkyl polyglycoside are added thereto, and the mixture is uniformly mixed to obtain the pigment layer intermediate; the pigment layer intermediate is uniformly coated on the base layer, and the pigment layer precursor is irradiated with an intensity of 80 mW / cm 2 The pigment layer is obtained by irradiating and curing for 6 seconds.

[0017] Preferably, the preparation method of the high-strength PP material is as follows: after the pigment layer is subjected to the plasma treatment, the mixed liquid is coated on its surface, and the surface-treated pigment layer is obtained after drying; the 4,5-dichloro-2-octyl-3-isothiazolinone, the 2,6-di-tert-butyl-p-methylphenol and the sodium hypophosphite are dissolved in ethanol to obtain an antibacterial liquid; the potassium dichromate solid is dissolved in water at 70°C, and then concentrated sulfuric acid is slowly added thereto to obtain an oxidizing liquid; the cubic boron nitride is added to the oxidizing liquid, heated and stirred for 2 hours, and then washed with water to obtain a surface-treated boron nitride; the antibacterial liquid is added to the surface-treated boron nitride, stirred at 50°C for 1 hour, and vacuum dried to obtain antibacterial boron nitride; the antibacterial boron nitride is added to the anti-wear layer raw material, mixed evenly, and coated on the surface of the surface-treated pigment layer, and cured for 3 seconds to obtain the anti-wear layer; the base layer, the pigment layer and the anti-wear layer together constitute the high-strength PP material from bottom to top.

[0018] On the other hand, the present invention provides an application of a high-strength PP material in a decorative film, and the application of the high-strength PP material in a decorative film on the surface of a wooden wardrobe; after the back of the base layer of the high-strength PP material is coated with a back adhesive, it is bonded to the surface of the wooden wardrobe and cured to obtain the decorative film; by changing the amount of raw materials for the base layer, the tensile strength of the high-strength PP material is 14-31MPa, the puncture resistance is 1.0-2.7N / µm, and the surface hardness is 2H-6H; by changing the amount of raw materials for preparing ethyl acrylic acid modified with pinacol diboric acid ester, the puncture resistance of the high-strength PP material is 1.5-3.0N / µm, and the wear rate is 1.3%- 2.8%; adjusting the dosage of cubic boron nitride, anti-wear layer and oxabicycloheptane, the puncture resistance of the high-strength PP material is 1.3-3.5N / µm, and the wear rate is 0.1%-2.6%; changing the preparation conditions of the surface-treated PP material, the puncture resistance of the high-strength PP material is 3.0-3.4N / µm, and the antibacterial zone diameter of the decorative film is 13.4-18.3mm; adjusting the component dosage ratio of the antibacterial liquid, the dosage of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane and the dosage of biboric acid pinacol ester, the antibacterial zone diameter of the decorative film is 17.0-20.6mm.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. By coating the surface of the plasma-treated PP material with a solution obtained by dissolving a chlorine-containing compound, adding activated alumina at the same time, controlling the type and amount of the chlorine-containing compound, and changing the amount of γ-alumina, at the selected reaction temperature, γ-alumina can act as a catalyst to promote the exchange reaction between the chloride ions of the chlorine-containing compound and the hydroxyl groups of the surface-treated PP material under the action of concentrated sulfuric acid, thereby bonding the chlorine-containing compound to the surface of the surface-treated PP material; on the other hand, γ-alumina and the chlorine-containing compound jointly improve the mechanical strength of the material.

[0020] 2. By reacting ethyl acrylic acid and pinacol diboron under the action of palladium chloride catalyst, the boron-boron bond of pinacol diboron is broken, and the boron element is transferred to the position of the chlorine element in ethyl acrylic acid. The prepared pinacol diboron modified ethyl acrylic acid is then polymerized with modified epoxy acrylate to prepare a pigment layer and an anti-wear layer. The final high-strength PP material has high strength and wear resistance.

[0021] 3. By modifying cubic boron nitride, impurities on its surface are removed under the action of potassium dichromate and concentrated sulfuric acid, and at the same time, it has a good adsorption and loading effect on antibacterial liquid. Cubic boron nitride has excellent extreme pressure wear resistance and compressive strength. By controlling its addition amount and reasonably adjusting the amount of anti-wear layer, the material has good puncture resistance and low wear rate. By adding oxabicycloheptane, the unsaturated double bonds in it copolymerize with the unreacted unsaturated double bonds in tripropylene glycol diacrylate and methacrylate glycidyl ether, further improving the overall strength of the high-strength PP material.

[0022] 4. By treating the polypropylene masterbatch with surfactant, the polypropylene molecules expand at a suitable temperature. The surfactant penetrates into the expanded polypropylene molecular chain under the action of the mixed solvent, and the final PP material has both polarity and non-polarity. Further plasma treatment increases the surface polarity of the PP material, promotes the penetration of antiseptic and antibacterial substances into the base layer, and the decorative film made of high-strength PP material penetrates into the surface of the wooden wardrobe, which has a long-lasting antibacterial effect on the basis of hardness.

[0023] 5. By adding antibacterial components to the pigment layer and the anti-wear layer, using cubic boron nitride to load the antibacterial liquid, adjusting the components in the antibacterial liquid, and changing the amount of end-capped silane, the water penetration into the decorative film made of high-strength PP material is reduced, thereby reducing the bulging and shedding of the decorative film on the surface of the wooden wardrobe, thereby reducing the risk of wardrobe corrosion. The amount of pinacol diborate used in the process of preparing high-strength PP material is jointly controlled, and the antibacterial property of the decorative film made of high-strength PP material is finally improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The puncture resistance and antibacterial performance results of Examples 33, 35-46 of the present invention and Comparative Examples 7 and 8 are shown in FIG. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] See also Figure 1 The present invention provides a high-strength PP material and its application in decorative film, and the technical solution is as follows: The substance information involved in the present invention is as follows: surfactin CAS: 24730-31-2; 4,5-dichloro-2-octyl-3-isothiazolinone CAS: 64359-81-5; epoxy acrylate CAS: 71281-65-7; ethyl acrylic acid CAS: 58-54-8; biboronic acid pinacol ester CAS: 615-925-0; 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy) )propyl] disiloxane CAS: 126-80-7; 2,6-di-tert-butyl-p-methylphenol (BHT) CAS: 128-37-0; tripropylene glycol diacrylate CAS: 42978-66-5; oxabicycloheptane CAS: 165727-60-6; ​​triarylsulfonium salt CAS: 8945-2-37-9; sesamin CAS: 607-80-7; the water-based pigment was purchased from BASF Chemical Co., Ltd.

[0027] Example 1 3.5 parts of surfactin are dissolved in a mixed solvent of ethanol and N,N-dimethylformamide to obtain a surfactin solution; the ratio of surfactin to the mixed solvent is 1:200; the ratio of ethanol to N,N-dimethylformamide in the mixed solvent is 3:2; 100 parts of polypropylene masterbatch are mixed with the surfactin solution to obtain a polypropylene dispersion; the polypropylene dispersion is heated to 170°C, melt-stirred under sealed conditions for 12 hours to obtain a modified polypropylene melt; the modified polypropylene melt is transferred to an extruder for extrusion and dried to obtain a PP material; 95 parts of PP materials were plasma treated at a speed of 4 m / min. -1, the discharge power is 1.5kw, and the surface treatment product of PP material is prepared; 4.3 parts of 4,5-dichloro-2-n-octyl-3-isothiazolinone are dissolved in ethanol to obtain a surface treatment solution; 2.5 parts of γ-alumina and 0.01 parts of concentrated sulfuric acid are added to the surface treatment solution, and ultrasonic treatment is performed for 15 minutes to obtain a mixed solution; the ratio of 4,5-dichloro-2-n-octyl-3-isothiazolinone to ethanol is 1:75; the mixed solution is evenly coated on one side of the surface treatment product of PP material, and dried at 60°C to obtain a base layer; 24.3 parts of ethyl acrylic acid are dissolved in N,N-dimethylformamide and dimethyl sulfoxide to obtain an ethyl acrylic acid solution; the usage ratio of ethyl acrylic acid to N,N-dimethylformamide and dimethyl sulfoxide is 1:100:200; the ethyl acrylic acid solution, 20.3 parts of biboric acid pinacol ester, 24.3 parts of potassium acetate and 0.6 parts of palladium chloride are placed in an oil bath pot at 85°C, react for 6 hours and then cool to room temperature to obtain biboric acid pinacol ester modified ethyl acrylic acid solution; 100 parts of water are added thereto, and then filtered, extracted with ethyl acetate, washed with water, dried with anhydrous sodium sulfate, and the solvent is removed to obtain biboric acid pinacol ester modified ethyl acrylic acid; all the reaction processes are carried out under nitrogen protection; 19.4 parts of epoxy acrylate were placed in a three-necked flask, the temperature was set to 70°C, 3.2 parts of concentrated sulfuric acid, 3 parts of ferric chloride and 5 parts of benzophenone were added thereto under stirring, and the mixture was refluxed for 5 hours to obtain modified epoxy acrylate; 65 parts of ethyl acrylic acid modified with pinacol diboron and 20.3 parts of azobisisobutyronitrile were added to the modified epoxy acrylate, and the mixture was refluxed for 5 hours to obtain a pigment layer precursor; 29.0 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane were added to the pigment layer precursor, and 1.5 parts of concentrated sulfuric acid, raise the temperature to 80°C, continue the reaction for 6 hours, filter and dry to remove the solvent, add 12.0 parts of tripropylene glycol diacrylate, 3 parts of triethylenetetramine, 5.1 parts of glycidyl methacrylate, 3.0 parts of sesamin, 2.3 parts of triarylsulfonium salt, 25 parts of water-based pigment (including but not limited to permanent orange and phthalocyanine blue, which can be selected according to actual use requirements) and 2.0 parts of alkyl polyglycoside, mix evenly to obtain a pigment layer intermediate; evenly apply the pigment layer intermediate on the base layer, and irradiate with an intensity of 80mW / cm 2 Irradiate and cure for 6 seconds to obtain a pigment layer; After the pigment layer is subjected to plasma treatment, a mixed liquid is coated on its surface, and a surface-treated pigment layer is obtained after drying; 8.6 parts of 4,5-dichloro-2-octyl-3-isothiazolinone, 10 parts of BHT and 5 parts of sodium hypophosphite are dissolved in 500 parts of ethanol to obtain an antibacterial liquid; 25 parts of potassium dichromate solid are dissolved in 50 parts of water at 70°C, and then 450 parts of concentrated sulfuric acid are slowly added thereto to obtain an oxidizing liquid; 50 parts of cubic boron nitride are added to the oxidizing liquid, heated and stirred for 2 hours, and then washed with water to obtain a surface-treated Boron nitride; add antibacterial liquid to the surface treated boron nitride, stir at 50°C for 1h, and vacuum dry to obtain antibacterial boron nitride; add antibacterial boron nitride to 20 parts of anti-wear layer raw materials, mix well and apply it on the surface of the surface treated pigment layer, and cure for 3s to obtain an anti-wear layer; the base layer, pigment layer and anti-wear layer are arranged in order from bottom to top to form a high-strength PP material; the difference between the anti-wear layer raw material and the pigment layer intermediate raw material is that the water-based pigment is replaced by an equal amount of oxabicycloheptane, and the other components and amounts remain unchanged.

[0028] Example 2-12 is different from Example 1 in that the following preparation conditions are changed, as shown in Table 1.

[0029] Table 1 Changes in conditions during the base preparation process

[0030] Comparative Example 1 Different from Example 1, no chlorine-containing compound is added.

[0031] Comparative Example 2 Different from Example 1, no γ-alumina was added.

[0032] Comparative Example 3 Different from Example 1, drying was carried out at 25°C.

[0033] Embodiment 13 The high-strength PP materials prepared in Examples 1-12 and Comparative Examples 1-3 were subjected to mechanical property tests. The specific test methods are as follows: the tear resistance of plastics was tested with reference to GB / T 16578.1-2008 "Determination of tear resistance of plastic films and sheets Part 1: Trouser tear method", and the test speed was 220 mm / min. At the same time, the puncture strength and surface hardness were tested, and the final test results are shown in Table 1.

[0034] The high-strength PP material prepared by the present invention has a tensile strength of 14-31MPa, a puncture resistance of 1.0-2.7N / µm, and a surface hardness of 2H-6H. After the surface of the PP material is treated with plasma, the surface of the material is provided with abundant hydroxyl and carboxyl groups, and then a chlorine-containing compound is coated on the surface. Under the action of a certain temperature, concentrated sulfuric acid and γ-alumina, the chlorine-containing compound and the material undergo ion exchange, so that the chlorine-containing compound is connected to the material through a chemical bond, thereby improving the overall strength of the material. As time goes by, the chlorine-containing compound gradually penetrates into the interior of the PP material, reacts with the surfactant therein, and further improves the mechanical properties of the material. The results of Examples 1-4 show that with the increase in the amount of 4,5-dichloro-2-n-octyl-3-isothiazolinone, the tensile strength shows a trend of decreasing, increasing and then decreasing, the puncture resistance shows an overall increasing trend, and the surface hardness gradually increases. Chlorine-containing compounds are connected to materials through chemical bonds. On the one hand, as the amount increases, its hardness and puncture resistance increase. However, when the amount increases to a certain extent, as shown in Example 4, due to its longer alkyl group, this flexible group and rigid group reach a certain balance, then the tensile strength no longer increases, but the puncture strength increases. The results of Examples 3, 5-7 show that with the increase in the amount of γ-alumina, the puncture resistance gradually increases, and the surface hardness gradually increases. As shown in the results of Example 6, the surface hardness is 6H. Under the action of concentrated sulfuric acid, the catalytic activity of γ-alumina is improved, which promotes the reaction of chlorine-containing compounds and the surface treatment of PP materials. In addition, γ-alumina has a strong hardness. Its use not only promotes the reaction, but also improves the overall hardness of the PP material. Therefore, in Comparative Example 2, γ-alumina is not added, and the puncture resistance is significantly reduced. The results of Examples 7-9 show that only when the reaction temperature is controlled within the range of 55-70°C, the high-strength PP material has high tensile strength, high puncture resistance and high surface hardness. The results of Examples 7 and 10 show that the puncture resistance is improved by replacing 4,5-dichloro-2-n-octyl-3-isothiazolinone with fenpropimorph. This is because fenpropimorph contains more rigid benzene ring structures, so the hardness is increased and the puncture resistance effect is increased. The results of Examples 10-12 show that the mechanical strength of the material is the best when the type and amount of chlorine-containing compounds, the amount of γ-alumina and the drying temperature are controlled within an appropriate range. As shown in Example 12, the puncture resistance is the highest and the tensile strength is relatively high. Comparative Example 1 does not add chlorine-containing compounds, so the performance of the material is reduced. The drying temperature of Comparative Example 3 is too low, the reaction is not complete, and the performance of the high-strength PP material is reduced.

[0035] Examples 14-23 Different from Example 12, the following preparation conditions are changed, as shown in Table 2.

[0036] Comparative Example 4 Different from Example 14, palladium chloride was not added.

[0037] Comparative Example 5 The difference from Example 12 is that the pinacol diboronate is replaced by an equal part of phenylboric acid.

[0038] Table 2 Changes in the preparation conditions of ethyl acrylic acid modified with biboric acid pinacol ester

[0039] Embodiment 24 The high-strength PP materials prepared in Examples 14-23 and Comparative Examples 4 and 5 were tested for puncture resistance and wear rate to evaluate the strength and wear resistance of the materials. The wear rate was calculated as follows: , where m1 is the initial mass of the high-strength PP material and m0 is the mass of wear. The test results are shown in Table 2.

[0040] The high-strength PP material prepared by the present invention has a puncture resistance of 1.5-3.0N / µm and a wear rate of 1.3%-2.8%. The results of Examples 12 and 14-17 show that with the increase in the amount of ethacrylic acid, the puncture resistance tends to gradually increase. The rigid structure contained in ethacrylic acid is bonded to the system with chemical bonds, so that the overall hardness of the high-strength PP material is improved, the puncture resistance is enhanced, and the wear rate basically shows a downward trend. The results of Examples 17-19 show that with the increase in the amount of bis(pinacol diboric acid) ester, the puncture resistance tends to increase first and then decrease, and the wear rate gradually decreases. Bis(pinacol diboric acid) ester is grafted into ethacrylic acid through chemical reaction, wherein the boron element of bis(pinacol diboric acid) ester can form a protective film on the surface of the material under pressure and wear conditions, thereby improving the wear resistance of the material. The results of Examples 18, 20-23 show that as the amount of palladium chloride increases, the amount of palladium chloride is within the range of 0.2-0.6 parts, and the puncture resistance and wear rate do not change significantly. When the amount of palladium chloride in Example 23 is 1.0 parts, the puncture resistance is the highest and the wear rate is the lowest. The amount of catalyst is controlled within a reasonable range. On the one hand, it catalyzes the reaction process of biboric acid pinacol ester and ethyl acrylic acid, and prevents the unreacted raw materials from being precipitated during use, thereby improving the puncture resistance and reducing the wear rate. Comparative Examples 4 and 5 do not add palladium chloride and replace biboric acid pinacol ester with equal parts of phenylboric acid, respectively. The puncture resistance and wear rate of Comparative Example 4 decrease, but the puncture resistance of Comparative Example 5 increases, and the wear rate increases compared with the embodiment. This is because both phenylboric acid and biboric acid pinacol ester have the effect of improving the wear rate of system materials. Phenylboric acid itself has a certain strength and can improve the strength of the system, but it cannot be combined with the system through chemical reaction, so the wear resistance is reduced.

[0041] Examples 25-33 Different from Example 23, the following preparation conditions are changed, as shown in Table 3.

[0042] Comparative Example 5 Different from Example 23, cubic boron nitride was not added.

[0043] Comparative Example 6 Unlike Example 23, no oxabicycloheptane was added.

[0044] Embodiment 34 The high-strength PP materials prepared in Examples 25-33 and Comparative Examples 5 and 6 were tested for puncture resistance and wear rate. The specific test method was carried out with reference to Example 24. The final test results are shown in Table 3.

[0045] Table 3 Changes in the amount of cubic boron nitride, anti-wear layer and oxabicycloheptane

[0046] The high-strength PP material prepared by the present invention has a puncture resistance of 1.3-3.5N / µm and a wear rate of 0.1%-2.6%. The results of Examples 23, 25-27 show that with the increase in the amount of cubic boron nitride, the puncture resistance gradually increases. The layered structure of cubic boron nitride gives it high strength, and its application in PP materials improves the puncture resistance of the material; the wear rate is further reduced. When cubic boron nitride responds to external pressure, its layers are displaced and staggered, which buffers and resists the pressure, thereby improving the wear resistance of the material. The results of Examples 27-31 show that with the increase in the amount of anti-wear layer, the puncture resistance gradually increases, and the wear rate shows a decreasing trend overall. However, if the amount of anti-wear layer is too high, as shown in Example 31, the color of the pigment layer is covered. The results of Examples 30, 32, and 33 show that with the increase in the amount of oxabicycloheptane, the puncture resistance first increases and then tends to stabilize, and the wear rate shows a gradually decreasing trend. The unsaturated double bonds in oxabicycloheptane and the unreacted double bonds in the system are copolymerized under the action of free radical initiators and triarylsulfonium salts, further improving the overall strength and wear resistance of the high-strength PP material.

[0047] Examples 35-46 Different from Example 33, the following preparation method is changed, as shown in Table 4.

[0048] Table 4 Preparation conditions of PP surface treatment products

[0049] Comparative Example 7 Different from Example 33, no surfactin was added.

[0050] Comparative Example 8 Unlike Example 33, the PP material was not plasma treated.

[0051] Embodiment 47 The high-strength PP materials prepared in Examples 33, 35-46 and Comparative Examples 7 and 8 were subjected to puncture resistance strength test and antibacterial performance test, and the puncture performance was tested by referring to the method of Example 24. The back of the base layer of the high-strength PP materials prepared in Examples 33, 35-46 and Comparative Examples 7 and 8 was coated with adhesive, and then laminated and cured to obtain a decorative film on the surface of a wooden wardrobe. One month after lamination, the decorative film was peeled off from the wooden wardrobe to detect the inhibitory effect on mold. The final test results are shown in Tables 5 and Figure 1 shown.

[0052] Table 5 Test results of puncture resistance and antibacterial performance of high-strength PP materials prepared in Examples 33, 35-46 and Comparative Examples 7 and 8

[0053] Table 5 and Figure 1The results show that the puncture resistance of the high-strength PP material prepared by the present invention is 3.0-3.4N / µm, and the diameter of the antibacterial zone of the decorative film is 13.4-18.3mm. By using surfactant to modify the polypropylene masterbatch, at a suitable temperature, the surfactant penetrates into the expanded polypropylene molecular chain, and the surfactant molecules penetrate the entire molecule, increasing the polarity of the polypropylene masterbatch. The surface of the surfactant contains abundant carboxyl, ether and imino groups, which is conducive to the penetration of the components in the antibacterial liquid. The antibacterial liquid components penetrate into the part of the polypropylene masterbatch where the surfactant is located, and finally penetrate into the surface of the wooden wardrobe, with good antibacterial effect. The results of Examples 33, 35-37 show that as the dosage of surfactant increases, the puncture resistance does not change significantly, but the diameter of the antibacterial zone gradually increases, indicating that the antibacterial effect gradually increases. The aqueous part of the surfactant can combine with the lipid components of the mold cell membrane to destroy the integrity of the cell membrane; the hydrophilic part can combine with water molecules to cause the water inside the mold cell to lose water, thereby affecting the growth metabolism of the mold and inhibiting its growth. The results of Examples 37-39 show that as the temperature of the polypropylene dispersion increases, the diameter of the antibacterial zone increases first and then decreases. When the temperature is too high, the activity of the surfactant decreases. In addition, the molecular distance of the polypropylene molecules increases significantly at a higher temperature, and the dispersibility of the surfactant in it decreases. The polypropylene molecules shrink after high-temperature expansion and then at room temperature. If the expansion distance is too large, the surfactant will gather in the shrinkage process, reducing the antibacterial effect. The results of Examples 38, 40-43 show that by performing plasma treatment, changing the plasma treatment speed and discharge power, the surface polarity of the PP material increases, and by using air as the gas source, the material surface is activated, and the material surface is full of hydroxyl, carboxyl and carbonyl groups, thereby promoting the antibacterial substances in the antibacterial liquid to penetrate from the pigment layer and the anti-wear layer to the surface of the wooden wardrobe, improving the antibacterial effect. Under the conditions of Example 44, the antibacterial zone diameter reaches 18.3 mm, and the antibacterial effect is the best. Comparative Examples 7 and 8 were not added with surfactant and plasma treatment, respectively. The puncture resistance strength did not change significantly compared with the examples, and the antibacterial effect decreased.

[0054] Examples 48-57 Different from Example 44, the following preparation conditions were changed, as shown in Table 6. The components of the antibacterial liquid included 4,5-dichloro-2-n-octyl-3-isothiazolinone, BHT and sodium hypophosphite in sequence.

[0055] Comparative Example 8 Different from Example 44, 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane was not added.

[0056] Comparative Example 9 Different from Example 44, no pinacol diboronate was added.

[0057] Comparative Examples 10-12 In contrast to Example 44, only 23.6 parts of 4,5-dichloro-2-n-octyl-3-isothiazolinone, 23.6 parts of BHT and 23.6 parts of sodium hypophosphite were added.

[0058] Table 6 Changes in the dosage ratio of components, the dosage of siloxane and the dosage of pinacol diborate in the antibacterial solution

[0059] Embodiment 58 The high-strength PP materials prepared in Examples 48-57 and Comparative Examples 8-12 were tested for antibacterial properties. The test method was carried out in accordance with Example 47. The final test results are shown in Table 6.

[0060] The high-strength PP material prepared by the present invention is applied to a decorative film and has a good antibacterial effect, and the diameter of the antibacterial zone is 17.0-20.6 mm. The results of Examples 44, 48 and 49 show that, while maintaining a certain amount of sodium hypophosphite, the antibacterial effect changes by changing the composition ratio of 4,5-dichloro-2-octyl-3-isothiazolinone and BHT. The heterocyclic structure and active part in 4,5-dichloro-2-octyl-3-isothiazolinone can effectively destroy the DNA molecules in the mold, interfere with the synthesis of the mold cell wall and cell membrane, and have a good inhibitory effect on the mold; when used in conjunction with BHT, the hindered phenol structure in BHT preferentially plays an antioxidant role, removes free radicals, and improves the antibacterial effect. 4,5-dichloro-2-octyl-3-isothiazolinone then cooperates with BHT to achieve the effect of inhibiting mold; sodium hypophosphite has a long-lasting antibacterial effect, and the molecules are decomposed into phosphate ions and hydroxide ions, among which the phosphate ions can bind to the proteins and phosphatidylinositol on the mold cell membrane and cell wall, thereby reducing the permeability of the cell membrane and inhibiting the growth of mold. Examples 50 and 51 adjust the ratio of the three, among which the diameter of the antibacterial zone under the conditions of Example 50 is the largest and the antibacterial effect is the best. The results of Examples 50, 52-54 show that as the amount of 1,1,3,3-tetramethyl-1,3-bis[3-(epoxyethylmethoxy)propyl]disiloxane increases, the antibacterial effect continues to increase, the unsaturated double bonds of ethyl acrylic acid modified by bis-boronic acid pinacol ester undergo polymerization reaction with ethyl acrylic acid, and the unreacted carboxyl groups in ethyl acrylic acid are capped by silane, thereby preventing moisture from penetrating into the decorative film. The growth of mold requires sufficient humidity, and the reduction of moisture content inhibits its growth from external conditions. Comparative Example 8 does not add siloxane, so the diameter of the antibacterial zone decreases. The results of Examples 54-57 show that as the amount of bis-boronic acid pinacol ester increases, the diameter of the antibacterial zone gradually increases. The bis-boronic acid pinacol ester is applied to the decorative film. In addition to having an anti-wear effect, it also has the effect of reacting with mold DNA, destroying the activity of mold, or complexing with nutrients to prevent the reproduction of mold. Comparative Example 9 does not add bis-boronic acid pinacol ester, and the antibacterial effect decreases. Comparative Examples 10-12 only add one substance, and the diameter of the antibacterial zone is greatly reduced compared with the embodiment. In summary, the present invention controls the dosage ratio of the components in the antibacterial liquid so that each component synergistically inhibits the growth and reproduction of mold. By reasonably adjusting the dosage of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane and bis-boronic acid pinacol, the internal and external conditions work together to inhibit the growth of mold and have a good antibacterial effect.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength PP material, characterized in that: It includes the following components: base layer, pigment layer and anti-wear layer; The raw materials for preparing the base layer include 95 parts of PP material, 3.8-6.7 parts of chlorine-containing compound and 2.5-4.0 parts of γ-alumina in parts by mass; The raw materials for preparing the pigment layer include 65 parts of bis(pinacol)diboron acid ester-modified ethyl acrylic acid, epoxy acrylate, 28.0-30.4 parts of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane and 12.0 parts of tripropylene glycol diacrylate; The raw materials for preparing the anti-wear layer include 4,5-dichloro-2-n-octyl-3-isothiazolinone, 2,6-di-tert-butyl-p-methylphenol and sodium hypophosphite, 43-53 parts of cubic boron nitride, and 15-40 parts of the raw materials for the anti-wear layer; The raw materials for preparing the PP material include 3.0-5.0 parts of surfactin; The PP material is prepared at 170-190° C. The PP material is subjected to plasma treatment to obtain the base layer. The treatment speed of the plasma treatment is 0-5 m·min -1 , discharge power is 1.5-4kw; The base layer is dried at 25-70°C; The raw materials for preparing the ethyl acrylic acid modified with pinacol diborate include 22.0-25.2 parts of ethyl acrylic acid, 20.3-24.0 parts of pinacol diborate and 0.2-1.0 parts of palladium chloride; The components of the anti-wear layer raw material include 20-28 parts of oxabicycloheptane; In terms of parts ratio, the usage ratio of 4,5-dichloro-2-n-octyl-3-isothiazolinone, 2,6-di-tert-butyl-p-methylphenol and sodium hypophosphite is 5.6-8.6:8-13:5-7.4; The chlorine-containing compound is one of 4,5-dichloro-2-n-octyl-3-isothiazolinone and difenoconazole.

2. A high-strength PP material according to claim 1, characterized in that: The processing speed of the plasma treatment is 1-5 m·min -1 .

3. The high-strength PP material according to claim 1, characterized in that: The base layer is obtained by drying at 55-70°C.

4. The high-strength PP material according to claim 1, characterized in that: The preparation method of the PP material is as follows: dissolving the surfactant in a mixed solvent to obtain a surfactant solution; mixing a polypropylene masterbatch with the surfactant solution to obtain a polypropylene dispersion; heating the polypropylene dispersion, and melting and stirring it under sealed conditions for 12 hours to obtain a modified polypropylene melt; transferring the modified polypropylene melt to an extruder for extrusion and drying to obtain the PP material.

5. A high-strength PP material according to claim 4, characterized in that: The ratio of the surfactin to the mixed solvent is 1:200; the ratio of ethanol to N,N-dimethylformamide in the mixed solvent is 3:

2.

6. The high-strength PP material according to claim 1, characterized in that: The preparation method of the base layer is as follows: the PP material is subjected to the plasma treatment to prepare a PP material surface-treated product; the chlorine-containing compound is dissolved in ethanol to obtain a surface-treated solution; the γ-alumina and concentrated sulfuric acid are added to the surface-treated solution, and ultrasonic treatment is performed for 15 minutes to obtain a mixed solution; the ratio of the chlorine-containing compound to the ethanol is 1:75; the mixed solution is uniformly applied to one side of the PP material surface-treated product, and the base layer is obtained after drying.

7. The high-strength PP material according to claim 1, characterized in that: The preparation method of the bis(pinacol)diboron modified ethyl acrylic acid is as follows: dissolving the ethyl acrylic acid in N,N-dimethylformamide and dimethyl sulfoxide to obtain an ethyl acrylic acid solution; the usage ratio of the ethyl acrylic acid to the N,N-dimethylformamide and the dimethyl sulfoxide is 1:100:200; placing the ethyl acrylic acid solution, the bis(pinacol)diboron, potassium acetate and palladium chloride in an oil bath pot at 85°C, reacting for 6 hours and then cooling to room temperature to obtain the bis(pinacol)diboron modified ethyl acrylic acid solution; adding water to the bis(pinacol)diboron modified ethyl acrylic acid solution, filtering, extracting with ethyl acetate, washing with water, drying with anhydrous sodium sulfate, and removing the solvent to obtain the bis(pinacol)diboron modified ethyl acrylic acid.

8. The high-strength PP material according to claim 1, characterized in that: The preparation method of the pigment layer is as follows: the epoxy acrylate is placed in a three-necked flask, the temperature is set to 70°C, concentrated sulfuric acid, ferric chloride and benzophenone are added thereto under stirring, and the modified epoxy acrylate is refluxed for 5 hours to obtain the modified epoxy acrylate; the bis(pyridinium)boron acid ester-modified ethyl acrylic acid and azobisisobutyronitrile are added to the modified epoxy acrylate, and the pigment layer precursor is refluxed; the 1,1,3,3-tetramethyl-1,3-bis[3-(epoxyethylmethoxy)propyl]disiloxane is added to the pigment layer precursor, the concentrated sulfuric acid is added, the temperature is increased to 80°C, the reaction is continued for 6 hours, and after the solvent is removed by suction filtration and drying, the tripropylene glycol diacrylate, triethylenetetramine, methacrylic acid glycidyl ether, sesamin, triarylsulfonium salt, water-based pigment and alkyl polyglycoside are added thereto, and the mixture is uniformly mixed to obtain the pigment layer intermediate; the pigment layer intermediate is uniformly coated on the base layer, and the pigment layer precursor is irradiated with an intensity of 80 mW / cm 2 The pigment layer is obtained by irradiating and curing for 6 seconds.

9. The high-strength PP material according to claim 1, characterized in that: The preparation method of the high-strength PP material is as follows: after the pigment layer is subjected to the plasma treatment, a mixed liquid is coated on its surface, and a surface-treated pigment layer is obtained after drying; the 4,5-dichloro-2-n-octyl-3-isothiazolinone, the 2,6-di-tert-butyl-p-methylphenol and the sodium hypophosphite are dissolved in ethanol to obtain an antibacterial liquid; the potassium dichromate solid is dissolved in water at 70°C, and then concentrated sulfuric acid is slowly added thereto to obtain an oxidizing liquid; the cubic boron nitride is added to the oxidizing liquid, heated and stirred for 2 hours, and then washed with water to obtain a surface-treated boron nitride; the antibacterial liquid is added to the surface-treated boron nitride, stirred at 50°C for 1 hour, and vacuum dried to obtain antibacterial boron nitride; the antibacterial boron nitride is added to the anti-wear layer raw material, mixed evenly, and coated on the surface of the surface-treated pigment layer, and cured for 3 seconds to obtain the anti-wear layer; the base layer, the pigment layer and the anti-wear layer together constitute the high-strength PP material from bottom to top.

10. Application of high-strength PP material in decorative film, characterized in that: Application of the high-strength PP material in the decorative film on the surface of a wooden wardrobe; after the back of the base layer of the high-strength PP material is coated with adhesive, it is bonded to the surface of the wooden wardrobe and cured to obtain the decorative film; by changing the amount of raw materials for the base layer, the tensile strength of the high-strength PP material is 14-31MPa, the puncture resistance is 1.0-2.7N / µm, and the surface hardness is 2H-6H; by changing the amount of raw materials for the preparation of ethyl acrylic acid modified with pinacol diboric acid ester, the puncture resistance of the high-strength PP material is 1.5-3.0N / µm, and the wear rate is 1.3%-2.8%; by adjusting the amount of cubic boron nitride, anti- The amount of the grinding layer and oxabicycloheptane, the puncture resistance of the high-strength PP material is 1.3-3.5N / µm, and the wear rate is 0.1%-2.6%; the preparation conditions of the PP material surface treatment product are changed, the puncture resistance of the high-strength PP material is 3.0-3.4N / µm, and the antibacterial zone diameter of the decorative film is 13.4-18.3mm; the component dosage ratio of the antibacterial liquid, the dosage of 1,1,3,3-tetramethyl-1,3-bis[3-(oxiranylmethoxy)propyl]disiloxane and the dosage of biboric acid pinacol ester are adjusted, and the antibacterial zone diameter of the decorative film is 17.0-20.6mm.

Citation Information

Patent Citations

  • Industrialized synthetic method of vismodegib

    CN104496889A

  • Modified rubber asphalt and preparation method thereof

    CN111978746A

  • Adhesive for high-temperature-resistant process protective film and preparation method of adhesive

    CN114316859A

  • Polypropylene decorative film with adhesive film layer as well as preparation method and application of polypropylene decorative film

    CN115873523A

  • Vinyl borate modified acrylic resin film-forming agent, preparation method thereof and universal primer

    CN116874657A